Generalized Errors in Variables Regression - Casson, M. C. (Review of Economic Studies, 1974)
Journal Article Generalized Errors in Variables Regression Get access M. C. Casson M. C. Casson University of Reading Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 3, July 1974, Pages 347–352, https://doi.org/10.2307/2296754 Published: 01 July 1974